2005
DOI: 10.1177/154405910508400213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization by Electron Spin Resonance Spectroscopy of Reactive Oxygen Species Generated by Titanium Dioxide and Hydrogen Peroxide

Abstract: The influence of reactive oxygen species (ROS) on the surface modification of titanium implants and osseointegration is unclear. The aim of this study was to evaluate the ability of titanium dioxide (TiO2) to generate ROS in the presence of H2O2 and to determine whether any ROS thus generated play a role in osseointegration, as measured by electron spin resonance (ESR) spin-trapping with 5,5-dimethyl-1-pyrolline-N-oxide (DMPO). We demonstrate that TiO2 together with H2O2 generated hydroxyl radicals (HO*), as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 27 publications
1
60
0
Order By: Relevance
“…•OH radicals, forming hydrogen peroxide [1,9,17,[32][33][34][35][36][37][38][39]. Therefore, it may be suggested that regarding the ROX effect, hydrogen peroxide and superoxide anion production from ZnO NPs would not produce salient antibacterial effect.…”
Section: Possible Antibacterial Mechanism Of the Generation Of Reactimentioning
confidence: 99%
See 1 more Smart Citation
“…•OH radicals, forming hydrogen peroxide [1,9,17,[32][33][34][35][36][37][38][39]. Therefore, it may be suggested that regarding the ROX effect, hydrogen peroxide and superoxide anion production from ZnO NPs would not produce salient antibacterial effect.…”
Section: Possible Antibacterial Mechanism Of the Generation Of Reactimentioning
confidence: 99%
“…Superoxide anion radical is unlikely to cause any bactericidal effect as it is less toxic and is poorly permeating to cell membranes. [17,33,37,39,40].…”
Section: Possible Antibacterial Mechanism Of the Generation Of Reactimentioning
confidence: 99%
“…ROS are strong oxidants that induce oxidative damage in the cell membrane and/ or cell wall of bacteria 13) . Generally, HO • can be detected by electron spin resonance spectroscopy (ESR) using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a spintrapping agent 14) . Recently, there has been growing interest in the antimicrobial activity of photocatalytic effects 10) .…”
Section: Both Homentioning
confidence: 99%
“…• production was detected by ESR spectroscopy as described previously 14) . DMPO (88 mM, Labotec, Tokyo, Japan) was used as the spin-trapping agent.…”
Section: Analysis Of Homentioning
confidence: 99%
“…•-), and H2O2 are involved in the photocatalysis of TiO2 [14][15] . We have developed an in vitro electron spin resonance (ESR) method for detecting ROS, such as O2…”
Section: Introductionmentioning
confidence: 99%